THE TRAUMA OF TERRORISM: VIOLENCE OF THE PAST IN THE PRESENT - Elsaesser, Thomas (Revista Trama Interdisciplinar, 2016)
This article discusses the main ideas in my book German Cinema - terror and trauma: cultural memory since 1945, where the meaning of the Holocaust for post-war German movies is re-evaluated, in order to provide a reconsideration of Trauma Theory today. I argue that Germany’s attempts to “dominate the past” can be seen both as a failure and an achievement, making it appropriate to speak of an ongoing “guilty management” that includes not only Germany, but Europe as a whole.